Bahasa Inggris - Vita Arumsari; Rikawati Rikawati (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
The low level of financial inclusion for the poor becomes a time bomb amid Islamic finance growth as an alternative and way of life, particularly for those who believe in the application of Islamic tenets in finance. Further, the evolving of fully-fledged Islamic Financial Non-Bank Institutions, particularly Islamic Microfinance Financial Institutions (IMFIs) are one of the myriad ways in alleviating poverty. Indonesia, with the highest number of the Muslim population in the world, can reduce the poverty percentage by using Islamic social funds, namely infaq, zakah, shadaqoh and waqf. This study sheds light on how to optimise the Islamic social fund benefit for improving the poor’s quality of life; both by injecting money to provide them with a business skill and to feed people them who are poor. We use meta-analysis method to recap different findings related to maximise the usage of Islamic social funds across a different point of view, hence a fit mechanism is found to be applied. It found that Islamic social funds can be used to sustain the fund whilst enabling the poor for generating income by integrating the fund with economics activities.